Presidential Decree-Law No 78/2013 On Granting A Special Raise To The State Civil Servants = قرار رئيس جمهورية مصر العربية بالقانون رقم 78 لسنة 2013 بمنح العاملين بالدولة علاوة خاصة - Egypt; The middle east library for economic services, translator. (2025)
presidential decree-law no 78/2013 on granting a special raise to the state civil servants قرار رئيس جمهورية مصر العربية بالقانون رقم 78 لسنة 2013 بمنح العاملين بالدولة علاوة خاصة